The Truth About Mrs Marshall - Jenkins, Terry (Petits Propos Culinaires, 2018)
We are all familiar today with the names of celebrity chefs. They can be so well-known that a first name is enough to identify them: two from Britian that immediately spring to mind are Nigella and Delia. Their surnames, Lawson and Smith, are unnecessary. In the Victorian era another celebrity cook was born with the surname Smith. She achieved fame, however, under her married name: Mrs Agnes Bertha Marshall, and was more famous in her day than Mrs Beeton. She published cookery books, lectured and gave public demonstrations on the subject. She edited a magazine called The Table and, with her husband, ran a cookery school in Mortimer Street, Westminster. She popularized the making of ice-cream with her patent inventions, and is credited with devising the first ice-cream cone for one of her recipes. But, as so often happens, her name and achievements faded from public memory after her death in 1905. This article augments what we know about Mrs. Marshall.